Effect of Different Terpene-Containing Essential Oils on the Proliferation of Echinococcus granulosus Larval Cells - Albani, Clara María; Denegri, Guillermo María; Elissondo, María Celina (Interdisciplinary Perspectives on Infectious Diseases, 2014)
Human cystic echinococcosis remains a major public health problem on several countries and the treatment strategies are not solved. The aim of the present work was to determine the in vitro effect of thymol and Mentha piperita, M. pulegium, and Rosmarinus officinalis essential oils on the proliferation of E. granulosus larval cells. Isolated cells and cellular aggregates were obtained from hydatid cyst’s germinal layer and exposed to 1, 5, and 10 μg/ml of thymol and the different essential oils for 7 days. Drug effect was evaluated using test viability and scanning electron microscopy. Control cell culture viability was 2.1 x 106 (100%) after 7 days of incubation. At day 7, thymol 5 μg/ml caused a reduction in cell viability of 63% and the essential oils of M. piperita 10 μg/ml, M. pulegium 10 μg/ml, and R. officinalis 10 μg/ml produced a reduction in the viability of 77, 82, and 71%, respectively. Moreover essential oils caused reduction in cell number, collapsed cells, and loss of normal tridimensional composition of the aggregates. Due to the inhibitory effect caused by essential oils on E. granulosus cells we suggested that it would be an effective means for suppression of larval growth.